An Overview of the Potential for Pharmacokinetic Interactions Between Drugs and Cannabis Products in Humans - Dolly Andrea Caicedo; Clara Pérez-Mañá; Magí Farré; Esther Papaseit (Pharmaceutics)
Cannabis is the most commonly used illicit substance worldwide. Recent years have seen an increase in cannabis consumption, and with new approvals and therapeutic indications, there are challenges in minimizing the risks and interactions between cannabis-based products, cannabis prescription drugs, other approved prescription drugs, and other substances of abuse. Thus, identifying the enzymes metabolizing cannabinoid drugs and their relationship with other prescription drugs is crucial for understanding the potential interactions and effects of their simultaneous use. This article offers a comprehensive review of cannabis and the pharmacokinetic interactions between cannabis products, cannabis prescription drugs, and other approved prescription drugs, as well as other substances of abuse. It also compiles existing evidence of these interactions and describes the clinical outcomes associated with the inhibition or induction of various enzymes.